Tumor location and parameter estimation by thermography - Agnelli, Juan Pablo (2011)
In non-invasive thermal diagnostics, accurate correlations between the thermal image on skin surface and interior human physiology are often desired, which require general solutions for the bioheat equation. In this study an estimation methodology is presented to determine unknown thermophysical or geometrical parameters of a tumor region using the temperature profile on the skin surface that may be obtained by infrared thermography. To solve these inverse problems a second order finite difference scheme was implemented to solve the bioheat Pennes equation with mixed boundary conditions in two and three dimensions. Then, the Pattern Search algorithm was used to estimate the different parameters by minimizing a fitness function involving the temperature profiles obtained from simulated or clinical data to those obtained by the finite different scheme.